Household accounting during the COVID-19 pandemic in phenomenology perspective - Dewi, Ni Putu Diah Sinthia; Suputra, I Dewa Gede Dharma; Sudana, I Putu; Gayatri, Gayatri (Linguistics and Culture Review, 2022)
The purpose of this research is to find out the role of household accounting in financial management and how the awareness, knowledge and readiness of a family in facing the COVID-19 pandemic crisis. This study uses a phenomenological approach to describe phenomena in the form of the same life experiences experienced by a number of people regarding the application of household accounting during the COVID-19 pandemic crisis. The themes found show that the application of household accounting has maximum benefits if it is applied in managing family finances before the COVID-19 pandemic occurs. If the application of household accounting is done well, it will avoid the difficulties of the COVID-19 pandemic crisis. Practically, the application of household accounting is something that must be considered and applied before and during the COVID-19 pandemic crisis. This research provides an overview of howthe role of household accounting if it was implemented before the COVID-19 pandemic occurred and what benefits would a family receive if implementing household accounting before and during the COVID-19 pandemic.